PENGUATAN PERAN HAKIM PENGADILAN AGAMA DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PUU-X/2012 - Siti Nurhayati (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
The Constitutional Court has agreed to annul the explanation of Article 55 (2) of the Law No 21 of 2008 on Islamic Banking. This explanation has caused conflict of dualism in the litigation process of default ad fraud cases of Islamic Banking. Previously, both Religious Court and Civil Court claim to have the competency to settle cases of Islamic Banking although according to Article 49 of the Law no 3 of 2006 on Religious Court the right has be granted to Religious Court. After the Counstitutional Court‟s decision, there should be no choice of forum in settling the cace of Islamic Banking. Thus, judges of Religious Court need to prepare for this.